Why nature is good to think, feel and live by in the Joban divine speeches: some psychological perspectives on the worth of exposure to wild animals - Viviers, Hennie (Old Testament essays, 2017)
The Biophilia Hypothesis has emphasised our innate attraction to the natural world, where we come from. Modern psychologies (e.g. developmental, emotional and environmental) have built on this and have highlighted the worth of being exposed to nature. Developmentally it has been shown how exposure to nature enhances cognitive, emotional and moral development in discovering the self. Emotionally it is especially the emotion of "awe" (wonderment born out of vastness and difficult to grasp) that leads to ego-transcendence, humbleness and oneness with nature. From the environmental perspective the fascination with the non-human environment can be restorative, calming and leading to contemplation and reflection. The pre-scientific Joban poet has intuitively grasped these emphases of modern research and celebrated nature and wild animals (unique in the HB) as good to think, feel and live by. The main character Job, however, seems not to have accepted this.